Research on the Application of Multi-scale & Multi-sensor Fusion Algorithm in MEMS Gyroscope Data Processing - Zhu, Hongjie (Journal of physics. Conference series, 2021)
The application of multi-scale and multi-sensor data fusion algorithm in sensor data processing, especially the data fusion of MEMS gyroscope, can greatly improve the accuracy after fusion. Based on this, this paper first analyzes the concept of multi-scale multi-sensor data fusion, then studies the application status of multi-scale multi-sensor data fusion, and finally gives the application of multi-scale multi-sensor data fusion algorithm in MEMS gyroscope data processing.